EKSISTENSI HAK PENGELOLAAN ATAS TANAH (HPL) DAN REALITAS PEMBANGUNAN INDONESIA - Elita Rahmi (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Management Right on Land (HPL) is right outside in Act No. 5 of 1960 on Basic Regulation on Agrarian Principles (Undang-undang Pokok Agraria/UUPA) that grow and develop in accordance with the demands of the development. Rights that has existed since the colonial era already formulated in a special regulation, so that the holders of HPL with are third parties who utilize HPL within the law and morals. Development held in Indonesia still requires the existence of HPL, due to limited government funds and the empowerment of government agencies central government and local government. HPL may become a test of the right control of the country. Are the economically weak have a place in existence in order to compensate parties who HPL always